The Influence Of Green Creativity On Sustainable Business Performance Thru Green Competitive Advantage As A Mediating Variable (Study on MSMEs in the Food and Beverage Sector in Bandar Lampung) - Agustinus Adventino Sulistyawan; RR. Erlina; Nurul Husna (International Journal of Economics, Business and Innovation Research, 2026)
This research aims to analyze the influence of Green Creativity on Sustainable Business Performance with Green Competitive Advantage as a mediating variable in the food and beverage SMEs in Bandar Lampung. The background of the research is based on the increasing demand for sustainable business practices in the MSME sector, but there are still limitations in translating green creativity into competitive advantage. The research uses a quantitative approach with a sample of 158 culinary MSME actors who implement environmentally friendly practices. A five-point Likert scale questionnaire was employed for data collection, and the data were subsequently analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) version 4.0. The results demonstrate that Green Creativity positively and significantly impacts Sustainable Business Performance as well as Green Competitive Advantage, yielding a path coefficient value of 0.833. Green Competitive Advantage has a significant positive effect on Sustainable Business Performance with a coefficient of 0.398 and partially mediates the effect of Green Creativity on Sustainable Business Performance with an indirect coefficient of 0.331. UMKM actors are advised to optimize environmentally-based creativity and build green competitive advantage to enhance sustainable business performance.